An evaluation of the role of NKG2C+ natural killer cells in protection from cytomegalovirus DNAemia early following allogeneic stem cell transplantation. Issue 5 (16th September 2013) - Muñoz‐Cobo, Beatriz; Giménez, Estela; Solano, Carlos; de la Cámara, Rafael; Nieto, José; López, Javier; Amat, Paula; Garcia‐Noblejas, Ana; Navarro, David
Abstract The role of natural killer (NK) cells in affording protection against human cytomegalovirus (CMV) in allogeneic stem cell transplant recipients is largely unknown. The current study was aimed at determining whether NKG2C+ NK cells confer protection from CMV DNAemia early following transplantation in patients lacking mono and polyfunctional CMV pp65 and IE‐1‐specific CD4+ and CD8+ T‐cell responses, as measured by flow cytometry for intracellular cytokine staining. Fourteen out of the 36 patients included in this study developed CMV DNAemia between days +30 and +60 after transplant. Three patients did so after day +60. Peripheral blood levels of CD56brightCD16−/low and CD56dimCD16+ NKG2C+ NK cells measured at day +30 and at day +60 in patients who had or had not subsequent CMV DNAemia did not differ significantly. In addition, no significant correlation was found between CD56brightCD16−/low (σ = −0.229; P = 0.39) and CD56dimCD16+ (σ = −0.285; P = 0.28) NKG2C+ NK‐cell levels and initial plasma CMV DNA loads. In summary, the data presented do not support a direct implication of NKG2C+ NK cells in preventing the development of CMV DNAemia or modulating the magnitude of CMV replication at early stages during episodes of CMV DNAemia in allogeneic stem cell transplant patients with unreconstituted CMV‐specific T‐cell responses. J. Med. Virol. 86:806–811, 2014. © 2013 Wiley Periodicals, Inc.